Structural Basis for Phospholyase Activity of a Class III Transaminase Homologue. (31st October 2016) - Cuetos, Anibal; Steffen‐Munsberg, Fabian; Mangas Sanchez, Juan; Frese, Amina; Bornscheuer, Uwe T.; Höhne, Matthias; Grogan, Gideon
Abstract: Pyridoxal‐phosphate (PLP)‐dependent enzymes catalyse a remarkable diversity of chemical reactions in nature. A1RDF1 from Arthrobacter aurescens TC1 is a fold type I, PLP‐dependent enzyme in the class III transaminase (TA) subgroup. Despite sharing 28 % sequence identity with its closest structural homologues, including β‐alanine:pyruvate and γ‐aminobutyrate:α‐ketoglutarate TAs, A1RDF1 displayed no TA activity. Activity screening revealed that the enzyme possesses phospholyase (E.C. 4.2.3.2) activity towards O‐ phosphoethanolamine (PEtN), an activity described previously for vertebrate enzymes such as human AGXT2L1, enzymes for which no structure has yet been reported. In order to shed light on the distinctive features of PLP‐dependent phospholyases, structures of A1RDF1 in complex with PLP (internal aldimine) and PLP⋅ PEtN (external aldimine) were determined, revealing the basis of substrate binding and the structural factors that distinguish the enzyme from class III homologues that display TA activity. Abstract : Enzyme evolution and catalytic diversity : The pyridoxal‐phosphate‐dependent class III transaminase homologue A1RDF1 does not catalyse transamination reactions, but rather the elimination of phosphate from O ‐phosphoethanolamine. We describe the structural determinants of reaction specificity, with consequences for studies on the human phospholyase AGXT2L1, an important enzyme in phospholipid metabolism.